Paraconsistentization and many-valued logics - Souza, Edelcio G. de (2020)
This paper shows how to transform explosive many-valued systems into paraconsistent logics. We investigate especially the case of three-valued systems showing how paraconsistent three-valued logics can be obtained from them.